Developing a Differentiated Learning Module for Islamic Religious Education to Support the Implementation of the Merdeka Curriculum - Agung; Muhadditsir Rifa'i (International Journal of Education and Humanities, 2026)
This study addresses the limited availability of teaching modules that accommodate the diverse learning needs of students in Islamic Religious Education (PAI), particularly within the framework of the Merdeka Curriculum. These differences—ranging from learning styles and comprehension levels to student motivation—often go unaddressed in conventional instructional materials, leading to suboptimal learning outcomes. The objective of this research is to develop a PAI teaching module based on differentiated learning that is valid, practical, and effective for implementing the Merdeka Curriculum. The study employs the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as its methodological framework. Observation and needs analysis were conducted to identify variations in students’ learning styles, which informed the module’s design. The results of the validation process indicate that the module achieves a high level of feasibility across content, presentation, language, and graphical aspects. Validators awarded very high average scores for the module’s alignment with the Merdeka Curriculum, conceptual depth, and contextual relevance. Moreover, the module is deemed effective in enhancing student engagement through interactive and contextual learning strategies. Nevertheless, minor areas for improvement remain, particularly in content depth and spelling accuracy. The implications of this study underscore the necessity of targeted teacher training in differentiated instruction to ensure the sustainability of inclusive and adaptive educational practices. By providing a ready-to-use, evidence-based PAI module, this research supports the successful implementation of the Merdeka Curriculum and promotes equitable learning opportunities for all students